Recent coarsening of sediments on the southern Yangtze subaqueous delta front: A response to river damming. (1st March 2018) - Yang, H.F.; Yang, S.L.; Meng, Y.; Xu, K.H.; Luo, X.X.; Wu, C.S.; Shi, B.W.
Abstract: After more than 50, 000 dams were built in the Yangtze basin, especially the Three Gorges Dam (TGD) in 2003, the sediment discharge to the East China Sea decreased from 470 Mt/yr before dams to the current level of ~140 Mt/yr. The delta sediment's response to this decline has interested many researchers. Based on a dataset of repeated samplings at 44 stations in this study, we compared the surficial sediment grain sizes in the southern Yangtze subaqueous delta front for two periods: pre-TGD (1982) and post-TGD (2012). External factors of the Yangtze River, including water discharge, sediment discharge and suspended sediment grain size, were analysed, as well as wind speed, tidal range and wave height of the coastal ocean. We found that the average median size of the sediments in the delta front coarsened from 8.0 µm in 1982 to 15.4 µm in 2012. This coarsening was accompanied by a decrease of clay components, better sorting and more positive skewness. Moreover, the delta morphology in the study area changed from an overall accretion of 1.0 cm/yr to an erosion of − 0.6 cm/yr. At the same time, the riverine sediment discharge decreased by 70%, and the riverine suspended sediment grain size increased from 8.4 µm to 10.5 µm. The annual wind speed and wave height slightly increased by 2% and 3%, respectively, and the tidal range showed no change trend. Considering the increased wind speed and wave height, there was no evidence that the capability of the China Coastal Current to transport sediment southward has declined in recent years. The sediment coarsening in the Yangtze delta front was thus mainly attributed to the delta's transition from accumulation to erosion which was originally generated by river damming. These findings have important implications for sediment change in many large deltaic systems due to worldwide human impacts. Highlights: The Yangtze delta front sediments coarsened from 8.0 µm in 1982 to 15.4 µm in 2012. This area changed from an overall accretion of 1.0 cm/yr to an erosion of − 0.6 cm/yr. Sediment decline resulting from river damming mainly contributed to the coarsening.